2009
DOI: 10.1002/jcc.21452
|View full text |Cite
|
Sign up to set email alerts
|

Bonding, aromaticity, and structure of trigonal dianion metal clusters

Abstract: Various isomers of the trigonal dianion metal clusters, X(3)(2-), X = Be, Mg, Ca, and their mono- and disodium complexes are optimized at the B3LYP/6-311+G(d) level. Different conceptual density functional theory based reactivity descriptors as well as the induced magnetic field values are calculated to understand the stability and aromaticity of these systems. Possibility of bond stretch isomerism is explored. Genetic algorithm results lend additional insights into the structures of these isomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 72 publications
2
24
0
Order By: Relevance
“…As the non‐zero value of the diradical character indicates the propensity of molecule toward triplet state, the molecule is also optimized at the triplet state at the same DFT level of theory. The triplet state is found to be more stable than the singlet state similar to the observation by Giri et al However, the molecule in the triplet state does not show bond‐stretch isomerism like its singlet analogue.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…As the non‐zero value of the diradical character indicates the propensity of molecule toward triplet state, the molecule is also optimized at the triplet state at the same DFT level of theory. The triplet state is found to be more stable than the singlet state similar to the observation by Giri et al However, the molecule in the triplet state does not show bond‐stretch isomerism like its singlet analogue.…”
Section: Resultssupporting
confidence: 84%
“…In a recent observation by Giri et al, the Be32 which is already known for its exceptional π‐aromatic behaviour, is claimed to be the new inclusion in the family of obscure examples of bond‐stretch isomers . In a number of works, the optimized geometry of Be32 in density functional theory (DFT) is found to come out with D 3 h symmetry where the bond lengths are 2.078 Å .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that the singlet state of the isolated cyclo ‐[Mg 3 ] 2− unit has exclusively σ‐aromaticity. Therefore, it seems that the interaction of Na + with this unit triggers off an unprecedented shift from the σ‐aromatic cluster to π‐aromatic species, NaMg 3 − and Na 2 Mg 3 23,121. It is worth mentioning here that the singlet state is not the ground state of cyclo ‐[Mg 3 ] 2− ; several accurate calculations have shown23,122 that actually the triplet state lies about 1–2 kcal/mol below the singlet state.…”
Section: Other Inorganic Clustersmentioning
confidence: 99%
“…One of such phenomena is the bond stretch isomerism, the isomer where more than one stable configuration of the same molecule exists with only major distinct difference in the bond length. Many instances of bond stretch isomerization have been theorized or reported for organic, main group elements, and transition metal compounds . Among such structures is the silicon analogues of bicyclo[1.1.0]butane (Scheme a).…”
Section: Introductionmentioning
confidence: 99%